Plasma membrane-localized SlSWEET7a and SlSWEET14 regulate sugar transport and storage in tomato fruits. (1st August 2021) - Zhang, Xinsheng; Feng, Chaoyang; Wang, Manning; Li, Tianlai; Liu, Xin; Jiang, Jing
Abstract: Sugars, especially glucose and fructose, contribute to the taste and quality of tomato fruits. These compounds are translocated from the leaves to the fruits and then unloaded into the fruits by various sugar transporters at the plasma membrane. SWEETs, are sugar transporters that regulate sugar efflux independently of energy or pH. To date, the role of SWEETs in tomato has received very little attention. In this study, we performed functional analysis of SlSWEET7a and SlSWEET14 to gain insight into the regulation of sugar transport and storage in tomato fruits. SlSWEET7a and SlSWEET14 were mainly expressed in peduncles, vascular bundles, and seeds. Both SlSWEET7a and SlSWEET14 are plasma membrane-localized proteins that transport fructose, glucose, and sucrose. Apart from the resulting increase in mature fruit sugar content, silencing SlSWEET7a or SlSWEET14 resulted in taller plants and larger fruits (in SlSWEET7a -silenced lines). We also found that invertase activity and gene expression of some SlSWEET members increased, which was consistent with the increased availability of sucrose and hexose in the fruits. Overall, our results demonstrate that suppressing SlSWEET7a and SlSWEET14 could be a potential strategy for enhancing the sugar content of tomato fruits.